PECULIARITIES AND FACTORS OF SOCIAL AND PSYCHOLOGICAL COMPETENCE HEADS OF EDUCATIONAL INSTITUTIONS - Бондарчук, О. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The features of socio-psychological competence of educational organizations’ managers are reflected in the article. The results of empiric peculiarities research and developmental factors of socio-psychological managers’ competence are presented